Keeping cabbage caterpillars under control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The green caterpillar of the Large Cabbage Worm Pieris rapae, with its narrow orange or yellow dorsal stripe, emerges from the soil for two to four weeks in order to feed on the leaves of many different species of cabbages. It then returns...